Será Prometeu culpado? Para uma mitanálise da modernidade educativa das Luzes - Alberto Filipe Araújo (Universidade do Minho, 2004)
This paper deals with Enlightenment Educational Modernity and most especially with its francophone variant. In the light of the pedagogic legacy of French Enlightenment the author will treat in a first instance, Enlightenment and Modernity, in a second instance the subject of The New Man will be dealt in the context of Enlightenment, and in a third point a myth-analysis will be carried about the educational modernity of Enlightenment. About the matter of whether Prometheus should be blamed or not, as far as a metaphor of reason is concerned, for leaving an indelible mark in educational modernity, the author replies to this question saying that instead of having an ethical problem we are confronted with an hermeneutical one, since such a vision of the myth is available only because of a particular reading.